Prevalence of lipase producer Aspergillus niger in nuts and anti-biofilm efficacy of its crude lipase against some human pathogenic bacteria - Asmaa S. Yassein (Nature Portfolio, 2021)
Abstract Nuts are the natural source of healthy lipids, proteins, and omega-3. They are susceptible to fungal and mycotoxins contamination because of their high nutritional value. Twenty-five species comprising 12 genera were isolated from 80 samples of dried fruits and nuts using the dilution plate method. Peanut recorded the highest level of contamination followed by coconut; almond and raisin were the lowest. Aspergillus was the most prevalent genus and A. niger, was the most dominant species. The morphological identification of the selected A. niger isolates as they were detected in high frequency of occurrence was confirmed by using 18SrRNA sequence. Ochratoxin biosynthesis gene Aopks was detected in the tested isolates. Lipase production by the selected A. niger isolates was determined with enzyme activity index (EAI) ranging from 2.02 to 3.28. A. niger-26 was the highest lipase producer with enzyme activity of 0.6 ± 0.1 U/ml by the trimetric method. Lip2 gene was also detected in the tested isolates. Finally, the antibacterial and antibiofilm efficiency of crude lipase against some human pathogens was monitored. Results exhibited great antibacterial efficacy with minimum bactericidal concentration (MBC) of 20 to 40 µl/100 µl against Escherichia coli, Pseudomonas aeruginosa, Proteus mirabilis, and Methicillin-resistant Staphylococcus aureus (MRSA). Interestingly, significant anti-biofilm efficacy with inhibition percentages of 95.3, 74.9, 77.1 and 93.6% was observed against the tested pathogens, respectively.